Comparison of the behavioral effects of exercise and high fat diet on cognitive function in adolescent rats - Lee, Jae-Min (J Exerc Rehabil, 2016)
Adolescence is a critical period for neurodevelopment, neuronal plasticity, and cognitive function. Experiences of adolescence can be exerted positive and negative effects on brain development. Physical exercise has a positive effect on brain function, which is characterized by improving memory function and increased neural plasticity. High fat diet (HFD)-induced obesity has a negative effect on brain function, which is characterized by insulin resistance and neuroinflammation and reduced microvessel constructure. Although the positive effect of exercise and negative effect of obesity on cognitive function have been documented, it has not been well whether comparison of the effects of exercise and obesity on cognitive function in adolescent rats. In the present study, we evaluated the behavioral changes related to cognitive function induced by exercise and obesity in adolescent rats. Male Wistar rats were randomly divided into three groups: the control group (CON), the exercise group (Ex), the high fat diet group (HFD). The HFD containing fat 60% was freely provided. The present results showed that spatial learning ability and short-term memory did not show significant effect exercise as compared to the control group. The present results showed that spatial learning ability and short-term memory was significantly decreased HFD-induced obesity group as compared to the control group. These results suggest that positive effect of physical exercise in adolescence rats may be exerted no significant effect on cognitive function. But, negative effect of HFD-induced obesity might induce cognitive impairment. HFD-induced obesity in adolescent rats may be used as an animal model of neurodevelopmental disorders.